PNPLA6/NTE, an Evolutionary Conserved Phospholipase Linked to a Group of Complex Human Diseases - Doris Kretzschmar (Metabolites, 2022)
Patatin-like phospholipase domain-containing protein 6 (PNPLA6), originally called Neuropathy Target Esterase (NTE), belongs to a family of hydrolases with at least eight members in mammals. PNPLA6/NTE was first identified as a key factor in Organophosphate-induced delayed neuropathy, a degenerative syndrome that occurs after exposure to organophosphates found in pesticides and nerve agents. More recently, mutations in PNPLA6/NTE have been linked with a number of inherited diseases with diverse clinical symptoms that include spastic paraplegia, ataxia, and chorioretinal dystrophy. A conditional knockout of PNPLA6/NTE in the mouse brain results in age-related neurodegeneration, whereas a complete knockout causes lethality during embryogenesis due to defects in the development of the placenta. PNPLA6/NTE is an evolutionarily conserved protein that in Drosophila is called Swiss-Cheese (SWS). Loss of SWS in the fly also leads to locomotory defects and neuronal degeneration that progressively worsen with age. This review will describe the identification of PNPLA6/NTE, its expression pattern, and normal role in lipid homeostasis, as well as the consequences of altered NPLA6/NTE function in both model systems and patients.